Challenges for Quality Assurance of Target Volume Delineation in Clinical Trials - Chang, Amy Tien Yee; Tan, Li Tee; Duke, Simon; Ng, Wai-Tong (Frontiers in Oncology, 2017)
In recent years, new radiotherapy techniques have emerged that aim to improve treatment outcome and reduce toxicity. The standard method of evaluating such techniques is to conduct large scale multi-centre clinical trials, often across continents. A major challenge for such trials is quality assurance to ensure consistency of treatment across all participating centres. Analyses from previous studies have shown that poor compliance and protocol violation have a significant adverse effect on treatment outcomes. The results of the clinical trials may therefore be confounded by poor quality radiotherapy. Target volume delineation is one of the most critical steps in the radiotherapy process. Many studies have shown large inter-observer variations in contouring, both within and outside of clinical trials. High precision techniques, such as intensity-modulated radiotherapy, image-guided brachytherapy and stereotactic radiotherapy have steep dose gradients, and errors in contouring may lead to inadequate dose to the tumour and consequently, reduce the chance of cure. Similarly, variation in organ at risk delineation will make it difficult to evaluate dose response for toxicity. This article reviews the literature on target volume delineation variability and its impact on dosimetry and clinical outcomes. The implications for quality assurance in clinical trials are discussed.